Clinical and morphological characteristics of enamel during pigment hypoplasia of tooth tissues. - Silenko, Yu. V.; Eroshenko, G. A.; Zhivotovsky, I. V.; Kuzenko, E. V. (Морфологія / Morphologia / Morfologìâ, 2018)
Background. Dystrophic changes in enamel and dentin occur as a result of metabolic disturbances in the hard tissues of the tooth and are characterized by its insufficient formation and mineralization, or excessive accumulation of pigments in the form of spots. The accumulation of pigment (qualitative and quantitative) is irreversible, that is, pigmentary dystrophy has no reverse development and remains in the enamel for life. Objectivе. To analyze the structural changes in tooth enamel in case of pigmentary dystrophy. Methods. After extraction, the teeth were embedded with Epon-812 epoxy. After polymerization, the obtained block was cut with a separating disk on thin sections 0.25 mm thick, an aluminum layer was applied to the preparations in vacuum and examined on a scanning electron microscope REM - 102E with an accelerating voltage of 30 kV. Results. It has been established that in case of chronic discolorites the enamel is partially fragmented, the phenomena of lysis of the enamel are determined. Lacunae are observed on the enamel-dentin border. Enamel preparations with congenital discolorations revealed a thickening of enamel prisms, mosaic expressiveness of Retzius lines. In exogenous pigmentary dystrophy, the main changes are established on the enamel surface. The phenomena of focal fragmentation, diffuse thinning of enamel prisms (atrophic changes) were observed. In endogenous pigmental dystrophy, the main changes are determined by the enamel-dentin boundary. Prisms are thinned and fragmented. Conclusion. Congenital dystrophy of pigment has a diffuse nature and affects the entire thickness of the enamel, which is caused by disorders in the process of histogenesis. With acquired discolorites, the localization of pathological changes depends on the etiology - endogenous, or exogenous. In endogenous pigmental dystrophy, morphological changes are found in the surface layers of enamel, developing as a result of disruption of the tertiary mineralization process, which create favorable conditions for the penetration of pigments by reducing the content of inorganic substances. In endogenous pigmental dystrophy, major changes develop in the deep layers of enamel adjacent to the dentine-enamel border. The source of pigment in this case is enamel spindles, which have a low content of inorganic substances and penetrate into the enamel on 1/3 of its thickness.